Pigmentary adverse effects of chemotherapeutic agents - Neerja Saraswat; Shekhar Neema; KPS Sengar (Wolters Kluwer Medknow Publications, 2019)
Introduction: Skin and mucosa are most susceptible to the adverse effects of chemotherapeutic agents due to rapid rate of proliferation. A wide array of these adverse effects has been reported in patients undergoing chemotherapy. Although mostly of cosmetic significance, few of these side effects may require alteration or suspension of therapy and reduce the likelihood of therapy completion. This study was undertaken to know the spectrum of skin pigmentary issues seen in these patients. Material and Methods: A total of 153 patients on chemotherapy for various malignancies from oncology department of the hospital were screened for cutaneous adverse effects over a period of 3 months. Relevant details and chemotherapy protocol followed were assessed. Cutaneous examination was done in daylight and photographs were taken. The data was analyzed at the end of 3 months. Results: Ninety-one (59.4%) patients had cutaneous adverse effects due to chemotherapeutic agents. Colorectal carcinoma was most common malignancy seen in 27 (29.6%) patients. Hand-foot hyperpigmentation was most common adverse effect seen in 67 (73.6%) patients followed by supravenous hyperpigmentation in 14 (15.3%), oral hyperpigmentation in four (4.3%), and flagellate hyperpigmentation and melisma-like pigmentation in three (3.2%). Capecitabine was most common drug resulting in hand-foot hyperpigmentation in 29 (43.2%) patients whereas docetaxel resulted in supravenous hyperpigmentation in five (35.4%) patients. Flagellate hyperpigmentation was seen with bleomycin and oral pigmentation exclusively noticed with capecitabine. Conclusion: Cutaneous adverse effects of chemotherapy are common but rarely reported. It is important to understand the entire spectrum of these side effects and allay the anxiety associated with them.